Physical Condition Profile Of Athletes Of SSB Kancil Mas Academy Class U-15 - Anggia Ningsih; Deden Akbar Izzuddin; Muhammad Arief Setiawan; Qorry Armen Gemael; Habibi Hadi Wijaya (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study focuses on the physical condition profile of athletes at the Kancil Mas Football School (SSB) U-15 category, to evaluate the level of physical fitness of athletes in supporting their optimal performance on the field. The physical conditions measured include endurance, speed, agility, and leg muscle explosive power, which are key elements in the game of football. This study uses a quantitative descriptive method, with instruments in the form of physical tests such as the Bleep Test, 30-meter run, shuttle run, and standing long jump. The results showed that most athletes had adequate physical condition, with the majority of athletes in the